Influence of Different Media Variety and Growth Regulator on Mycelial Colony Proliferation of Mushroom (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted at the Mushroom growth house and Tissue Culture Laboratory, Horticulture Demonstration and Training Centre (HDTC), Kewatkhali, Mymensingh during February to May, 2006 to investigate the mycelial colony proliferation of different mushroom species (Oyster (Pleurotus florida), Milky (Calocybe indica) and Button (Agaricus biporus)) in different media (viz. PDA, YPDA and MEA) and different combinations and concentrations ( 0, 1, 5, 10 and 20 ppm) of different growth regulators (IAA and NAA). As a media, the best mycelial growth of 9.34 cm was found in YPDA (Yeast Potato Dextrose Agar) at 21 DAI. As a variety, the best mycelial growth of 11.90 cm was performed by Oyster at 21 DAI. In case of combined effect of different media and variety for mycelial growth, the best growth (12.57 cm) was found in Oyster with YPDA media at 21 DAI. In case of growth regulator, the best mycelial growth of 5.50 cm was found at 21 DAI with 10 ppm IAA and 4.03 cm was found at   18 DAI with 5 ppm NAA and 5.38 cm at 21 DAI with control. In case of combined effect of IAA and NAA, the best mycelial  colony proliferation (6.72 cm) was found with 10 ppm IAA + 5 ppm NAA at 21 DAI. It may be concluded that among three varieties and media, Oyster was the best variety and YPDA was the superior media for mushroom cultivation. Malt extract supplemented with 10 ppm IAA+ 5 ppm NAA as found to be the best for mycelial colony proliferation of Button mushroom DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11586 J. Environ. Sci. & Natural Resources, 5(1): 223 227, 2012